The relationship between the knowledge factors of pregnant women and the incidence of hepatitis B - Hunam, Maria Marselina; Supriyanto, Supriyanto; Sutriswanto, Sutriswanto (ELECTRON (Journal of Science and Technology), 2025)
Hepatitis is caused by the hepatitis B virus and is a health problem throughout the world including in Indonesia, estimated to infect nearly two billion people in the world and around 350 million people are pregnant women, (World Health Organization). The factor of knowledge of pregnant women about the incidence of hepatitis B is closely related to a person's awareness of the risk of hepatitis infection. The study aims to determine the relationship between the knowledge factors of pregnant women and the incidence of hepatitis B in the work area of the Desideria Sandai Primary Clinic, Ketapang Regency. Comparative Analytical Research Design with Cross-Sectional approach, sampling using total sampling technique with a sample size of 40 pregnant women. This study uses primary data in the form of questionnaires given to pregnant women who conduct pregnancy checks at the Desideria Sandai Primary Clinic and are tested for Hepatitis B by the Rapid Test HbsAg method. The results of the Chi-Square Analysis showed significant relationship between the Knowledge Factor of pregnant women and the incidence of Hepatitis B at the Pratama Desideria Sandai ClinicKetapang Regency as evidenced by the p-value on the Fiscer Exact Test of 0.042 (<0.05). There is a significant relationship between the Knowledge factor of pregnant women and the incidence of Hepatitis B at the Pratama Desideria Sandai Clinic, Ketapang Regency.